A Layered Control Architecture of Sleep and Arousal - Chen, Michael C.; Sorooshyari, Siamak K.; Lin, Jian-Sheng; Lu, Jun (Frontiers in Computational Neuroscience, 2020)
Sleep and wakefulness are promoted not by a single neural pathway but via wake or sleep-promoting nodes distributed across layers of the brain. A layered subsumption model for arousal based on a common computational architecture is proposed. We suggest that each layer of the brain have sleep and wake computations driven by similar high-level architecture and processing units. Specifically, an interconnected wake-promoting system is suggested as driving arousal in each brain layer with the processing converging to produce the features of wakefulness. In contrast, sleep-promoting GABAergic neurons largely project to and inhibit wake-promoting neurons. We propose a general pattern of caudal wake-promoting and sleep-promoting neurons having a strong effect on overall behavior. However, while rostral brain layers contain weaker wake and sleep-promoting systems, they can subsume the activity of caudal brain layers to promote arousal. The two models presented in this work will propose computations for the layering and hierarchy. Through dynamic system theory several hypotheses are introduced for the interaction of controllers and systems that correspond to the different populations of neurons at each layer. The models will be drawn-upon to discuss future experiments to elucidate the structure of the hierarchy that exists among sleep-arousal architecture.